Investigating the effect of various lengths of bamboo straw on the mechanical properties of adobe - Balfaqih Ahmed; Baarimah Abdullah O.; Yafouz Ayman; Yahaya Fadzil Mat; Najah Ali (E3S Web of Conferences)
Adobe buildings are popularly used in different universe regions and comprise an important characteristic of the worldwide cultural heritage. Moreover, in recent years, ecological construction materials like bricks of adobe have become more economically vital. The advantages of using adobe as a main construction material include environment, economy, friendliness, good thermal with sound insulation, and perfect indoor air quality. Therefore, it is vital to investigate the adobe’s mechanical properties. This research aims to investigate the effect of different sizes of bamboo straw on adobe bricks, which is considered a process of seeking high-performance bricks in terms of compressive strength and flexural strength. The mixture utilized in this experimental research contains sand, clay, silt, and bamboo straw. Adobe bricks with bamboo straw were prepared along with a control mix. The brick size is 227 x 115 x 75 mm which consists of different percentages of bamboo straw 0.5%, 1%, and 1.5%. Meanwhile, the bamboo straw has different lengths of 30 mm, namely, short bamboo and 60 mm as long bamboo. 70 samples were tested out of which, 35 bricks samples were tested for compressive strength, whereas 35 bricks samples were tested for flexural test. By adding the bamboo straw reinforcement, the adobe compressive strength increased also the addition of short bamboo straw recorded the maximum compressive strength up to 3.41 MPa. A solid conclusion can be made that the samples constructed with short bamboo straw throughout the mix performed better than the samples with long bamboo straw in compressive strength test and for flexural strength short bamboo marked the best performance to the 1.0%.